Antibiotic residues in poultry and food safety risks in North Cotabato, Philippines (Asian Journal of Agriculture, 2025)
Abstract. Hadji Ibrahim AB, Jumao-As CM, Tampus AD, Tabugo SRM, Adamat LA, Jose MAI, Tanabe MEN, Amparado OA. 2025. Antibiotic residues in poultry and food safety risks in North Cotabato, Philippines. Asian J Agric 9: 463-471. Poultry production in North Cotabato, Philippines, remains a key agricultural sector, yet the extent of antimicrobial residue contamination in retail chicken meat is poorly documented. This study aimed to detect and quantify antibiotic residues in organic and non-organic chicken meat sold in public wet markets using liquid chromatography-tandem mass spectrometry (LC-MS/MS). Thirty-six whole dressed chickens (18 organic and 18 non-organic) were purchased across six municipalities, yielding 72 tissue samples (wings and legs). Six antibiotics namely doxycycline, enrofloxacin, norfloxacin, tilmicosin, amoxicillin, and trimethoprim/sulfamethoxazole were targeted. Doxycycline was the most frequently detected compound, present in 100% of non-organic and 50% of organic samples. Fluoroquinolones (enrofloxacin/norfloxacin) and tilmicosin (macrolide) were detected exclusively in non-organic leg tissues at frequencies of 66.7% and 50%, respectively. Residue concentrations ranged from 0.05), Chi-square tests revealed significant differences in detection frequency by production type (p
Keywords: Antimicrobial residues, chicken meat, LC-MS/MS, North Cotabato, QuEChERS method